We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
199
2
avatar+1016 

 

 

 May 26, 2018
 #1
avatar+974 
+2

Since the equation is already factored, we just need to consider the three cases:

 

To solve this problem, we need to understand that the product of zero and any number is equal to zero. 

 

Case 1: 3x = 0 

 

3x = 0 

x = 0 

 

Case 2: x + 4 =0

 

x + 4 = 0 

x= -4 

 

Case 3: x - 6

 

x - 6 = 0 

x = 6 

 

The three solutions are 0, -4, and 6. 

 

I hope this helped,

 

Gavin

 May 26, 2018
 #2
avatar+7445 
+1

3x(x+4)(x-6) = 0

x = 0 or x+4 = 0 or x-6 = 0

x = 0 or x = -4 or x = 6

 May 26, 2018

5 Online Users

avatar